The Role of Land Deed Officials (PPAT) in the Inheritance Process of Uncertified Land with Acquisition Value of Tax Object (NPOP) in Indonesia - Mohamad Nur Fikri; Nia Maulina (UNIVERSITAS PAKUAN, 2026)
This study examines the role of Land Deed Officials (Pejabat Pembuat Akta Tanah/PPAT) in the inheritance process of uncertified land with respect to the determination of the Acquisition Value of Tax Object (Nilai Perolehan Objek Pajak/NPOP) in Indonesia. Land, as a vital resource, requires legal certainty to prevent disputes and ensure proper administration, particularly in cases of inheritance where land ownership is transferred from the deceased to heirs. However, the existence of uncertified land creates legal and administrative challenges, including difficulties in proving ownership, determining rightful heirs, and establishing the taxable value of the land. This research employs a normative legal method using statutory and conceptual approaches by analyzing relevant laws, regulations, and legal doctrines related to land law, inheritance law, and taxation in Indonesia. The study finds that PPAT plays a crucial role not only in drafting authentic deeds but also in verifying ownership evidence, ensuring the legality of inheritance processes, and assisting in determining the NPOP as the basis for calculating land and building acquisition tax (BPHTB). In cases of uncertified land, the responsibilities of PPAT become more complex due to the need for additional verification and coordination with relevant authorities. The findings indicate that PPAT contributes significantly to ensuring legal certainty, administrative order, and tax compliance in the transfer of land rights through inheritance. Nevertheless, the lack of land certification remains a major obstacle that can potentially lead to legal disputes. Therefore, strengthening land registration systems and increasing public awareness regarding the importance of land certification are essential to enhance legal certainty in land inheritance processes in Indonesia. Keywords: Land Deed Official (PPAT), inheritance, uncertified land, legal certainty, NPOP, land registration.